PERAN VARIABEL EFIKASI DIRI SEBAGAI MODERATOR PENINGKATAN MOTIVASI BERPRESTASI GURU - Eny Lestari; Arief Yulianto; Sugi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education plays a strategic role in preparing superior human resources to support the Golden Indonesia Vision 2045. Teachers play a central role as the spearhead of improving the quality of education, with achievement motivation being an important factor influencing their professional quality and performance. Unfortunately, this motivation is still relatively low, as seen from the lack of teacher participation in self-development, learning innovation and professional programs. This study aims to analyze the factors that influence teachers' achievement motivation, both internal (self-efficacy) and external (principal leadership, school organizational climate, and academic supervision). The study was conducted on 268 public junior high school teachers in the ex Kawedanan Candiroto area, Temanggung Regency, Central Java, using a total sampling technique. The variables studied include achievement motivation as the dependent variable; principal leadership, school organizational climate, and academic supervision as independent variables; and self-efficacy as a moderating variable. Data were collected through a closed questionnaire that had been tested for validity and reliability, then analyzed using SEM-PLS through the SmartPLS program. The results of the analysis show that all independent variables have a positive and significant effect on teacher achievement motivation. In addition, self-efficacy acts as a moderator that strengthens the influence of the three external variables. Implication of this finding